Determinant of Foreign Direct Investment Inflows in Asean Countries - Sasana, Hadi; Fathoni, Salman (Universitas Negeri Semarang, 2019)
Foreign Direct Investment (FDI) believed to be one of the instruments to reduce gap between the rich and the poor countries has considered Asian countries destination, including ASEAN Region. The aim of this study was to analyze factors affecting FDI in ASEAN countries (Cambodia, Indonesia, Malaysia, Philippines, Thailand, and Vietnam) during 2007-2016. The method used to analyze the data was multiple linear regression. The results indicated that market size, government integrity, and infrastructure quality positively affected FDI; wages and exchange rates negatively affected FDI; while, economic crisis had negative effect only in Malaysia. Meanwhile, economic openness, tax rate, and interest rate did not affect FDI inflow in ASEAN countries.